Penerapan Metode English Auction pada Aplikasi Lelang Item Inventory - Permana, Denny Riandhita Arief; Anwar, Muchamad Taufiq; Abas, Sidiq Waskito (Jurnal Ilmiah Sains dan Teknologi, 2024)
PT Indra Karya is one of the state-owned companies in the field of construction consultants. PT Indra Karya, in carrying out its business processes, still uses traditional methods in documenting, For this reason, PT Indra Karya is trying to digitize existing business processes for the application of modern technology, in line with the president's appeal regarding IndustryOne of the efforts made to realize this is the auction inventory system. In designing the application, it requires an application framework with its model, namely Laravel as a framework used for design methods and using a prototyping model to facilitate the design and evaluation stages. In the design process, using the PHPMyadmin database, which functions as a storage medium and data that will be processed in the application activity, the result of the design is an auction inventory application that can run on an online platform by adhering to the English auction method. The process of transferring inventory items can be done easily and can bring value and instill a digital culture in employees.